E-cadherin in contact inhibition and cancer - Mendonsa, Alisha M.; Na, Tae-Young; Gumbiner, Barry M. (Oncogene, 2018)
E-cadherin is a key component of the adherens junctions that are integral in cell adhesion and maintaining epithelial phenotype of cells. Homophilic E-cadherin binding between cells is important in mediating contact inhibition of proliferation when cells reach confluence. Loss of E-cadherin expression results in loss of contact inhibition and is associated with increased cell motility and advanced stages of cancer. In this review we discuss the role of E-cadherin and its downstream signaling in regulation of contact inhibition and the development and progression of cancer.